2010
DOI: 10.1108/00251741011043902
|View full text |Cite
|
Sign up to set email alerts
|

Organizational support for intrapreneurship and its interaction with human capital to enhance innovative performance

Abstract: Purpose -The main purpose of this paper is to investigate the direct and interactive effects of organizational support and human capital on the innovative performance of companies. Individual effects of the organizational support dimensions, namely: management support for generating and developing new business ideas, allocation of free time, convenient organizational structures concerning, in particular, decentralization level or decision-making autonomy, appropriate use of incentives and rewards, and toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
1
18

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(194 citation statements)
references
References 85 publications
(93 reference statements)
5
137
1
18
Order By: Relevance
“…Previous literature has already studied the necessity of creating an inner environment that is conducive to internal entrepreneurship and individual commitment to sustainable corporate entrepreneurship (Alpkan et al, 2010). A successful intrapreneurial spirit can only be possible if a suitable internal support climate is established where intrapreneurs engage in opportunity-seeking entrepreneurial behaviours, as in the case of independent entrepreneurs discovering important challenges and opportunities (Zahra, 1991;Barringer & Bluedorn, 1999;Jeong et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature has already studied the necessity of creating an inner environment that is conducive to internal entrepreneurship and individual commitment to sustainable corporate entrepreneurship (Alpkan et al, 2010). A successful intrapreneurial spirit can only be possible if a suitable internal support climate is established where intrapreneurs engage in opportunity-seeking entrepreneurial behaviours, as in the case of independent entrepreneurs discovering important challenges and opportunities (Zahra, 1991;Barringer & Bluedorn, 1999;Jeong et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…According to recent empirical studies on different cultures around the world, investments made in improve human capital and education seem to provide an increase in the organizational innovativeness (Alpkan et al, 2010). Similarly, Chen et al (1998) identified a correlation between the level of entrepreneurial intention and the number of management courses taken by students.…”
Section: Knowledge As a Resourcementioning
confidence: 99%
“…A suitable organisational milieu for intrapreneurial activities to flourish innovative human capital requires behavioural patterns for pioneering innovative ideas in their products, operational and managerial processes, structures and markets (Alpkan et al, 2010). According to De Jong & Wennekers, 2008), there are several important elements on how to establish a suitable environment and organisational architecture that focus on innovation for intrapreneurship.…”
Section: Pro-innovativeness Organisational Architecture and Innovativmentioning
confidence: 99%
“…It was also considered as characteristic of the organization (Foss et al, 2013). Studies have tended to the extent to which a person generates ideas depends on the perception of the work environment (Damanpour, 1991;Axtell et al, 2000;Hornsby et al, 2009;Alpkan et al, 2010). On the other hand, physical work environment consists of several items such as lighting, space or size of working area, the quality of air, the temperature, the layout, and another physical setting in the organization (Cartwright and Cooper, 1997).…”
Section: Work Environmentmentioning
confidence: 99%